(untitled) (Bangladesh Journal of Zoology, 2021)
The investigation was conducted on the present situation of fish biodiversity and abundance of fish fauna at two different points of Madhumati River at Mohammadpur upazilla under Magura district from October 2018 to September 2019. A total of 83 species of fresh water fish species were recorded belonging to 58 genera of 28 families under 11 orders. Cypriniformes was recorded as the dominant order comprising 26 species constituting 31% of the total. According to IUCN 59% of fish species were Least Concern, 12% were Vulnerable, 11% were Endangered, 9% were Near Threatened, 1% of each were Data Deficient and Critically Endangered locally, and 7% Exotic fish species were also enlisted. Annual value of Shannon diversity index (H) was 1.974 and Sipmson diversity index (λ) was 0.272 which indicate highest diversity of fish was in March. Annual Margalef’s richness index (D) was 6.654 and Pielou’s evenness index (E) was 0.447 denote highest richness was in November and evenness was in March. The river was found to have moderate type of diversity in terms fish species composition. Bangladesh J. Zool. 49(1): 19-34, 2021